COVID 19 therapies and anti-cancer drugs: A systematic review of recent literature. (August 2020) - Di Lorenzo, Giuseppe; Di Trolio, Rossella; Kozlakidis, Zisis; Busto, Giuseppina; Ingenito, Concetta; Buonerba, Luciana; Ferrara, Claudia; Libroia, Annamaria; Ragone, Gianluca; Ioio, Concetta dello; Savastano, Beatrice; Polverino, Mario; et al.
Abstract: Background: It is reasonable to think that cancer patients undergoing chemotherapy, targeted therapy or immunotherapy could have a more aggressive course if positive for Coronavirus disease CoV-2 (COVID- 19). Methods: We conducted a literature review on https://www.ncbi.nlm.nih.gov/pubmed/, https://scholar.google.com, www.arxiv.org, www.biorxiv.org, of all articles published using the keywords COVID-19 therapy or treatment and cancer until May 2, 2020. A total of 205 articles were identified and 53 were included in this review. Results: We describe the ongoing COVID-19 therapies that should be known by oncologists and highlight the potential interactions with antineoplastic drugs, commonly used in clinical practice. The main drug interactions were found with tocilizumab, ruxolitinib and colchicine. Conclusions. The literature provides an inconclusive picture on potential preferred treatments for COVID-19 and their interactions with antineoplastic agents. Future clinical trials are needed to better understand the interactions between different drugs in the context of COVID-19 pandemic.